Adoption of Unified Payments Interface in the Rural Livelihoods of Tenkasi District. - Maheswari, S. Uma; Devi, . V. Jaisudha (Journal of Neonatal Surgery, 2025)
India’s transition from a physical-centric to a digital-centric society has been significantly accelerated by the Digital India Programme, with the Unified Payments Interface (UPI) emerging as one of its most transformative outcomes. Introduced in 2016, UPI has revolutionized financial transactions by enabling instant, secure, and interoperable payments across banks and platforms, positioning India as a global leader in digital payments. This study, conducted in Tenkasi District, examines the adoption of UPI in rural livelihoods, focusing on its role in enhancing financial inclusion, reducing dependence on cash, and integrating marginalized communities into the formal economy. Using purposive sampling, data were collected from 230 respondents and analyzed through descriptive statistics. The findings reveal that UPI is widely adopted for daily financial transactions, savings, and money transfers, while weaker adoption is observed in areas such as selling products, accessing government subsidies, and trust in reliability. Barriers such as limited digital literacy, inadequate institutional support, technical glitches, and language accessibility further restrict usage. The study concludes that while UPI has rapidly expanded and become essential in rural financial practices, strengthening trust, usability, institutional integration, and awareness is crucial to ensure inclusive, reliable, and sustainable adoption in rural Tamil Nadu